Internal Promoters and Their Effects on the Transcription of Operon Genes for Epothilone Production in Myxococcus xanthus - Wang, Ye; Yue, Xin-jing; Yuan, Shu-fei; Hong, Yu; Hu, Wei-feng; Li, Yue-zhong (Frontiers in Bioengineering and Biotechnology, 2021)
The biosynthetic genes for secondary metabolites are often clustered into giant operons with no transcription terminator before the end. The long transcripts are frangible and the transcription efficiency declines along with the process. Internal promoters might occur in operon to coordinate the transcription of individual genes, but their effects on the transcription of operon genes and the yield of metabolites have been less investigated. Epothilones are a kind of anti-tumor polyketides synthesized by seven multifunctional enzymes encoded by a 56-kb operon. In this study, we identified multiple internal promoters in the epothilone operon. We performed CRISPR-dCas9-mediated transcription activation of internal promoters, combined activation of different promoters, and activation in different epothilone-producing M. xanthus strains. We found that activation of internal promoters in operon was able to promote the gene transcription, but the activation efficiency was distinct from the activation of separate promoters. The transcription of genes in operon was influenced by not only the starting promoter but also internal promoters of the operon; internal promoters affected the transcription of following and neighboring upstream/downstream genes. Multiple interferences between internal promoters thus changed the transcriptional profile of operon genes and the production of epothilones. Better activation efficiency for the gene transcription and the epothilone production was obtained in the low epothilone-producing strain. Our results highlight that interactions between promoters in operon are critical for the gene transcription and the metabolite production efficiency.